Modelling ICU capacity under different epidemiological scenarios of the COVID-19 pandemic in three western European countries - McCabe, R; Kont, MD; Schmit, N; Whittaker, C; Løchen, A; Baguelin, M; Knock, E; Whittles, LK; Lees, J; Brazeau, NF; Walker, PGT; Ghani, AC; et al. (Oxford University Press, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has placed enormous strain on intensive care units (ICUs) in Europe. Ensuring access to care, irrespective of COVID-19 status, in winter 2020–2021 is essential.